THE EFFECT OF PANCURONIUM BROMIDE AS A MUSCLE RELAXANT ALONE OR COMBINATION WITH DIAZEPAM IN SHEEP - Abdalbari A. Alfars (Basrah Journal of Veterinary Research)
The effect of pancuronium bromide (0.025 mg/kg. B.W.) alone or combined with diazepam (1mg/Kg. I.V) were evaluated in six adult ewes. Pancuronium bromide alone exhibited a muscle relaxants effect, but without analgesia. All baseline measurements were taken before the administration the anesthetic agent and were repeated at 5,10,15,20 and 25 min. intervals after induction an aesthesia alone or combination with diazepam . it was found that heart rate decreased at 5 min.,but respiratory rate did change at 5-25 min. and it was significantly at 15,20 and 25 min. Pancuronium bromide – diazepam combination is responsible for declined respiratory rate and decumbency position in early stage. Pancuronium bromide – diazepam induce effective and safe an aesthesia for periods 45 minutes, due to competitive diazepam as a sedative effect of muscle relaxation. Adequate strength and duration of analgesia due to prevent impulse transmission histamine and ensured rapid and safe recovery